Transformation of the Ukrainian Economy in Conditions of the Crisis: some Results, Problems and Prospects - A. G. Pylin (Проблемы постсоветского пространства, 2020)
Over the past six years since the change of political power (in February 2014) and the new leadership of the country proclaimed the course towards Euro-Atlantic integration,Ukrainehas gone through the next and the largest crisis in its post-Soviet history. This crisis was the result of not only negative global (slowdown in global economic growth, falling demand and prices for traditional Ukrainian exports), but also regional (rupture of trade and economic ties withRussia) factors amid loss of part of the territory and military operations in the east countries. Such serious external and internal shocks greatly affected to the Ukrainian economy, which at the same time withstood and largely adapted to sharply changing conditions. However, it is not necessary to talk about any significant development of the country, about its structural and technological modernization, increasing competitiveness in this period. To achieve this goal, the new authorities ofUkrainewill need to make a lot of efforts, achieve consolidation of the entire Ukrainian society on the country’s strategic development, complete large-scale structural and institutional reforms, solve the Donbass problem and at least partially restore the destroyed humanitarian and economic ties withRussia.